SYNTHESIS, CHARACTERIZATION AND POLYMERIZATION OF NSUBSTITUTEDMALEIMIDYLACRYLATES - Al-Azzawi, Ahlam Marouf; Pyriadi, Thanun Mohammad; Al-Obaidi, Kafa Khalaf (Al-Nahrain Journal of Science, 2009)
Four N-(hydroxy phenyl) maleamic acids were prepared in high yields (90-95)% via reaction of maleic anhydride with ortho, meta and para amino phenols.Dehydration of the prepared maleamic acids via treatment with acetic anhydride and pyridine produced the corresponding N-(hydroxy phenyl ) maleimides in good yields (70-80)% .Esterification of the prepared imides with acryloyl chloride in the presence of triethyl amine gave the corresponding maleimidyl acrylates which inturn were polymerized free radically to produce new polyacrylates.The prepared compounds were characterized by FTIR, U.V and 1HNMR spectroscopy while thermal stability of the prepared polymers were investigated by (TG) and (DTA) thermal analysis.